Strategy of Teacher Competency Development Program in Madrasah Tsanawiyah - Rokhana Oktiasari; Hasyim Asyari; M. Afif Zamroni (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
The purpose of this article is to describe and analyze strategies, evaluations, and materials for competency development at Madrasah Tsanawiyah Darut Tauhid Driyoejo Gresik. The research method in this article is qualitative with a case study approach. The place of this research was conducted in Madrasah Tsanawiyah Darut Tauhid Driyoejo Gresik which is located at Jalan Raya Banjaran Driyorejo Gresik Village. The informants of this research were the head of the Madrasah, the head of the foundation, the deputy head of the madrasa, and several teachers. Data collection techniques with observation, interviews, and documentation. The results of this study are: 1) The material for the teacher competency development program that has been implemented at MTs Darut Tauhid consists of material for making teacher administration which includes four teacher competencies and material for using information techniques, namely making powerpoints, making google forms, making classrooms and using zoom applications. meetings; 2) The strategies used in teacher competency development are training, workshops, and Subject Teacher Consultations (MGMP); 3) Evaluation of coaching includes the coaching program that has been implemented, facilitators, coaching materials, participants, strategy for implementing the coaching program and budget.